2016
DOI: 10.1038/srep24394
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin triggers rhythmic electrical firing in hypothalamic GHRH neurons

Abstract: Hypothalamic growth hormone-releasing hormone (GHRH) neurons orchestrate body growth/maturation and have been implicated in feeding responses and ageing. However, the electrical patterns that dictate GHRH neuron functions have remained elusive. Since the inhibitory neuropeptide somatostatin (SST) is considered to be a primary oscillator of the GH axis, we examined its acute effects on GHRH neurons in brain slices from male and female GHRH-GFP mice. At the cellular level, SST irregularly suppressed GHRH neuron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 61 publications
(101 reference statements)
0
8
0
Order By: Relevance
“…This observation may explain lower basal GH levels in male than in female mammals ( Jansson et al, 1985 ), and also the sexually dimorphic GH pulsatile secretion ( Low et al, 2001 ). More recently, the negative regulation by SRIF of GHRH neuron electrical activity was decrypted using a GHRH–GFP transgenic model ( Osterstock et al, 2016 ). It revealed a sexual dimorphism, which is primarily attributable to a sex-dependent control of GABAergic and glutamatergic inputs by SRIF, rather than intrinsic differences in the GHRH neurons themselves.…”
Section: Somatostatin Receptormentioning
confidence: 99%
See 1 more Smart Citation
“…This observation may explain lower basal GH levels in male than in female mammals ( Jansson et al, 1985 ), and also the sexually dimorphic GH pulsatile secretion ( Low et al, 2001 ). More recently, the negative regulation by SRIF of GHRH neuron electrical activity was decrypted using a GHRH–GFP transgenic model ( Osterstock et al, 2016 ). It revealed a sexual dimorphism, which is primarily attributable to a sex-dependent control of GABAergic and glutamatergic inputs by SRIF, rather than intrinsic differences in the GHRH neurons themselves.…”
Section: Somatostatin Receptormentioning
confidence: 99%
“…Intriguingly, this is the opposite for SRIF inhibition of GABAergic (negative) inputs, being especially robust and synchronized in males. Both SST 1 and SST 2 are involved in GHRH neuron rhythmicity, but SST 1 receptors specifically transduce SRIF inhibitory control of GABAergic inputs, likely taking place at the presynaptic level ( Osterstock et al, 2016 ). Seven percent of neuropeptide Y–positive neurons in the ARC coexpress SST 1 mRNA, suggesting a direct interaction between the somatotropic axis and neuroendocrine regulatory loops of energy homeostasis ( Fodor et al, 2005 ).…”
Section: Somatostatin Receptormentioning
confidence: 99%
“…Transcriptional profiling of hypothalamic glucose-sensing neurons along with electrophysiological studies has revealed that hypoglycemia activated GHRH neurons ( 195 ). The electrical patterns that controlled the hypothalamic GHRH neurons have remained elusive while recently somatostatin has been found to bring about irregular suppression of the neuronal activity of GHRH neurons ( 196 ). In summary, it is the important role in GH secretion along with its involvement in nutritional and circadian feeding behavior that has made GHRH vital in integration and coordination of diverse aspects related to metabolism, growth and nutrient regulation ( 190 , 197 ).…”
Section: Growth Hormone–releasing Hormonementioning
confidence: 99%
“…However, results from other mammals, including female rats [Reviewed by Gahete et al ( 38 )], challenge the role of somatostatin in regulating GH rhythmicity. More recently, it has been demonstrated that somatostatin irregularly inhibits GHRH neurons in male and female mice, inducing sex–specific oscillatory patterns in the GHRH neural electrical activity ( 86 ). The sexual dimorphism in the GHRH oscillatory patterns induced by somatostatin seems dependent on the different actions of both glutamate and GABA neurons, and these differences could explain the distinctive GH secretion pattern between male and female mice ( 86 ).…”
Section: Main Hormonal Regulators Of Somatotrophs—ghrh and Somatostatmentioning
confidence: 99%